Modernization of reclamation agriculture management systems - Yurchenko, Irina; Bandurin, Mikhail; Bandurina, Inna (BIO web of conferences, 2021)
Today, a brand new strategy that can foster agricultural production is being shaped based on IT solutions. The paper characterizes the state and prospects for the development of digital farm management, the challenges of mastering digital innovations by agricultural enterprises and ways to tackle them at the present stage. A study is relevant due to the lack of a conceptual approach to the evolution of information digital systems in the sector of ameliorative economy in the context of growing requirements for environmental safety and competitiveness of agricultural production. The solutions to create a common information environment uniting an enterprise with suppliers of resources and consumers of products (services) are also increasingly relevant today. A methodological toolkit rests on some general scientific approaches, including analysis and synthesis, methods of deduction and systems analysis, cluster approach. After careful evaluation of automated processes at reclamation enterprises, there can be no doubt that it is necessary to improve the efficiency of information and technological support for management decisions by digital systems. The challenges are related to: lack of proper concept and methodology of modern digital systems, as well as procedures for the integration cooperation of information resources and a digital management system operations for managing them; unified algorithms for handling information; automation operations that meet the present management requirements; qualified experts encouraged to improve the use of digital technologies. The basic procedures for enhancing digital systems at enterprises include: analytical evaluation of current production situation, development of a functional design and model of the integrated digital system; creation of a mechanism for its implementation. In the process of transforming digital support for managerial actions, the following actions are possible: modification of the structure of existing processes; automation of conventional technological and organizational production procedures; alignment of existing processes subject to the technologies being integrated; identification of new opportunities for operations.